Modulation of the pupillary response by the content of visual working memory - Zokaei, N; Board, A; Manohar, S; De Ozorio Nobre, A (National Academy of Sciences, 2019)
Studies of selective attention during perception have revealed modulation of the pupillary response according to the brightness of task-relevant (attended) vs. -irrelevant (unattended) stimuli within a visual display. As a strong test of top-down modulation of the pupil response by selective attention, we asked whether changes in pupil diameter follow internal shifts of attention to memoranda of visual stimuli of different brightness maintained in working memory, in the absence of any visual stimulation. Across 3 studies, we reveal dilation of the pupil when participants orient attention to the memorandum of a dark grating relative to that of a bright grating. The effect occurs even when the attention-orienting cue is independent of stimulus brightness, and even when stimulus brightness is merely incidental and not required for the working-memory task of judging stimulus orientation. Furthermore, relative dilation and constriction of the pupil occurred dynamically and followed the changing temporal expectation that 1 or the other stimulus would be probed across the retention delay. The results provide surprising and consistent evidence that pupil responses are under top-down control by cognitive factors, even when there is no direct adaptive gain for such modulation, since no visual stimuli were presented or anticipated. The results also strengthen the view of sensory recruitment during working memory, suggesting even activation of sensory receptors. The thought-provoking corollary to our findings is that the pupils provide a reliable measure of what is in the focus of mind, thus giving a different meaning to old proverbs about the eyes being a window to the mind.